Mutations in gamma adducin are associated with inherited cerebral palsy. Issue 6 (December 2013) - Kruer, Michael C.; Jepperson, Tyler; Dutta, Sudeshna; Steiner, Robert D.; Cottenie, Ellen; Sanford, Lynn; Merkens, Mark; Russman, Barry S.; Blasco, Peter A.; Fan, Guang; Pollock, Jeffrey; Green, Sarah; et al.
<x xml:space="preserve">Abstract</x> Objective Cerebral palsy is estimated to affect nearly 1 in 500 children, and although prenatal and perinatal contributors have been well characterized, at least 20% of cases are believed to be inherited. Previous studies have identified mutations in the actin‐capping protein KANK1 and the adaptor protein‐4 complex in forms of inherited cerebral palsy, suggesting a role for components of the dynamic cytoskeleton in the genesis of the disease. Methods We studied a multiplex consanguineous Jordanian family by homozygosity mapping and exome sequencing, then used patient‐derived fibroblasts to examine functional consequences of the mutation we identified in vitro. We subsequently studied the effects of adducin loss of function in Drosophila. Results We identified a homozygous c.1100G>A (p.G367D) mutation in ADD3, encoding gamma adducin in all affected members of the index family. Follow‐up experiments in patient fibroblasts found that the p.G367D mutation, which occurs within the putative oligomerization critical region, impairs the ability of gamma adducin to associate with the alpha subunit. This mutation impairs the normal actin‐capping function of adducin, leading to both abnormal proliferation and migration in cultured patient fibroblasts. Loss of function studies of the Drosophila adducin ortholog hts confirmed a critical role for adducin in locomotion. Interpretation Although likely a rare cause of cerebral palsy, our findings indicate a critical role for adducins in regulating the activity of the actin cytoskeleton, suggesting that impaired adducin function may lead to neuromotor impairment and further implicating abnormalities of the dynamic cytoskeleton as a pathogenic mechanism contributing to cerebral palsy. Ann Neurol 2013;74:805–814